2006
DOI: 10.4018/jswis.2006070104
|View full text |Cite
|
Sign up to set email alerts
|

Information Retrieval by Semantic Similarity

Abstract: Semantic Similarity relates to computing the similarity between conceptually similar but not necessarily lexically similar terms. Typically, semantic similarity is computed by mapping terms to an ontology and by examining their relationships in that ontology. We investigate approaches to computing the semantic similarity between natural language terms (using WordNet as the underlying reference ontology) and between medical terms (using the MeSH ontology of medical and biomedical terms). The most popular semant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(72 citation statements)
references
References 36 publications
0
65
0
1
Order By: Relevance
“…A better, more semantically aware similarity measure, such as the one described in [13], is likely to have a significant impact on the overall accuracy. To accommodate such a metric, the extracted semantic properties need to be accurately linked to the Semantic Web.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…A better, more semantically aware similarity measure, such as the one described in [13], is likely to have a significant impact on the overall accuracy. To accommodate such a metric, the extracted semantic properties need to be accurately linked to the Semantic Web.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…The evaluation of the semantic similarity methods indicated that this method is particularly effective, achieving up to 73% correlation with results obtained by humans [34]. An important observation and a desirable property of this method is that it tends to assign higher similarity to terms which are close together (in terms of path length) and lower in the hierarchy (more specific terms), than to terms which are equally close together but higher in the hierarchy (more general terms).…”
Section: The Amtex Methodsmentioning
confidence: 99%
“…Documents are represented by term vectors produced by AMTEx (v2.0) and MMTx respectively. Document matching is performed by Vector Space Model (VSM, [34]). Both methods (i.e., retrieval by AMTEx and MMTx vectors) are compared against retrieval using vectors of MEDLINE provided index term sets, i.e.…”
Section: Abstract-based Retrieval Experimentsmentioning
confidence: 99%
“…Applications to provide inexact search capabilities over ontologies or to improve classical information retrieval techniques have also been proposed, e.g., (Hliaoutakis, 2005;Varelas et al, 2005;Hliaoutakis et al, 2006;Kiefer et al, 2007;Sy et al, 2012;Pirró, 2012). In this context, semantic measures have also been successfully applied to learning tasks using Semantic Web technologies (D'Amato, 2007).…”
Section: Knowledge Engineering Semantic Web and Linked Datamentioning
confidence: 99%